2020
DOI: 10.20944/preprints202001.0024.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of Leaf Rust Resistance Source in Wheat Germplasm in Relation to Epidemiological Factors

Abstract: A comprehensive germplasm screening study of 855 wheat advanced lines was conducted at Wheat Research Institute, Ayub Agricultural Research Institute Faisalabad to identify new sources of leaf rust resistance during crop seasons 2015-2017. In primary evaluation, 112 advanced lines were selected having high phenotypic uniformity for further testing at wheat research Institute Faisalabad, a hotspot for leaf rust. The second round of evaluation exhibited 54 lines having durable type resistance against leaf rust. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Therefore, it is crucial to measure the relationship between epidemiological variables and leaf rust severity to detect its onset early on [ 46 , 47 ]. The present investigation found a significant correlation between epidemiological variables and leaf rust severity (%), which is in line with the findings of [ 10 , 13 ] who showed a significant relationship between leaf rust severity and environmental variables. The leaf rust severity (%) increased when the maximum temperature (17.8–26.8 °C) and minimum temperature (7.91–15.03 °C) increased during both rating seasons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is crucial to measure the relationship between epidemiological variables and leaf rust severity to detect its onset early on [ 46 , 47 ]. The present investigation found a significant correlation between epidemiological variables and leaf rust severity (%), which is in line with the findings of [ 10 , 13 ] who showed a significant relationship between leaf rust severity and environmental variables. The leaf rust severity (%) increased when the maximum temperature (17.8–26.8 °C) and minimum temperature (7.91–15.03 °C) increased during both rating seasons.…”
Section: Discussionsupporting
confidence: 93%
“…In March and April, the crop is severely infected with brown rust [ 8 ]. Following pathogen infestation, orange to brown colour, circular to oval-shaped pustules appeared on the upper epidermis of leaves [ 9 ].The rapid dissemination of brown rust infection occurs within a temperature range of 10–30 °C [ 10 ]. The pathogen is capable of infecting within 3 h during dew periods when the air temperature is at 20 °C [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results were in line with the findings of Prabhu et al, (1993) and Pretorious (1983) who identified the resistant sources against leaf rust epidemics on the basis of AUDPC. Similarly, during assessment of leaf rust resistance, Ali et al, (2020a), Ali et al, (2020b) and Khan et al, (2002) reported the same infection data as presented here. Characterization of epidemiological variables showed that all environmental conditions remained significant against disease development.…”
Section: Discussionsupporting
confidence: 80%
“…Tilt has a systemic mode of action with protective and curative functions with more fungal growth inhibiting rather than fungicidal properties. Most of the cultivated wheat varieties in central Asian countries are susceptible to stripe rust races (Sharma et al, 2013, Ali et al, 2020b and the growers manage the disease severity primarily through foliar application of fungicides. Generally, 41% grain yield increases due to disease protection by fungicide application therefore the wheat growers can greatly benefits from crop protection measures.…”
Section: Discussionmentioning
confidence: 99%